The pathophyiological role of aminoacyl-tRNA synthetases in digestive system diseases - Wusiman, Wugelanmu; Zhang, Zerui; Ding, Qiang; Liu, Mei (Frontiers in Physiology, 2022)
Aminoacyl-tRNA synthetases (ARSs) catalyze the ligation of amino acids to their cognate transfer RNAs and are indispensable enzymes for protein biosynthesis in all the cells. Previously, ARSs were considered simply as housekeeping enzymes, however, they are now known to be involved in a variety of physiological and pathological processes, such as tumorigenesis, angiogenesis, and immune response. In this review, we summarize the role of ARSs in the digestive system, including the esophagus, stomach, small intestine, colon, as well as the auxiliary organs such as the pancreas, liver, and the gallbladder. Furthermore, we specifically focus on the diagnostic and prognostic value of ARSs in cancers, aiming to provide new insights into the pathophysiological implications of ARSs in tumorigenesis.